Biochemistry and Genetics of Galactose Metabolism in Group H Streptococcus Strain Challis - Luginbuhl, Geraldine H. (1972)
Galactose-negative mutants of the group H Streptococcus strain Challis were obtained by treatment with nitrosoguanidine. Enzyme assays of extracts of these mutants revealed that 12 of the mutants were lacking one of the enzymes of the Leloir pathway. Thus, the Leloir pathway is the major means of galactose metabolism in strain Challis. In addition, uridyl diphosphate galactose pyrophosphorylase, a permease function, and at least one other function are required for the utilization of galactose. The enzymes of the Leloir pathway are induced by galactose and fucose; no compounds which act as repressors of these enzymes have been found, although the system appears to be sensitive to catabolite repression. Transformation was used to map the mutants. The genes for galactose-1-phosphate uridyl transferase and glucose-4-epimerase appear to be closely linked. Within the transferase gene, six mutations have been mapped. The permease function and the undetermined functions are not linked to the Leloir pathway.